2015
DOI: 10.1126/science.aaa8577
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Number-space mapping in the newborn chick resembles humans’ mental number line”

Abstract: Rugani et al . (Reports, 30 January 3015, p. 534) tested 3-day-old domestic chicks using an innovative experimental setup and demonstrate the presence of the mental number line. We raise concerns regarding this conclusion by highlighting the possible loopholes in the experimental design and the data analysis procedures. We further suggest auxiliary experiments that can substantiate the authors’ claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In English speaking humans, despite significant group level left-to-right orientations, as many as 25% of adult participants may show a reverse, right-to-left effect when viewing magnitude stimuli (Wood et al, 2008; Lazareva et al, in preparation). Interestingly, despite the presence of a group-level left-to-right spatial representation of magnitude for chicks (Rugani et al, 2015), more than half of individual chicks showed a right-to-left or nonsignificant orientation (Mangalam & Karve, 2015). This is consistent with our results that only about half of the observed slopes were in the negative, left-to-right orientation (cf.…”
Section: Discussionmentioning
confidence: 99%
“…In English speaking humans, despite significant group level left-to-right orientations, as many as 25% of adult participants may show a reverse, right-to-left effect when viewing magnitude stimuli (Wood et al, 2008; Lazareva et al, in preparation). Interestingly, despite the presence of a group-level left-to-right spatial representation of magnitude for chicks (Rugani et al, 2015), more than half of individual chicks showed a right-to-left or nonsignificant orientation (Mangalam & Karve, 2015). This is consistent with our results that only about half of the observed slopes were in the negative, left-to-right orientation (cf.…”
Section: Discussionmentioning
confidence: 99%
“…angalam and Karve claim that some confounds may violate the assumption of trials' independency of the measures and criticize the use of the Mann-Whitney test instead of the binomial test (1). We have now analyzed chicks' performance focusing on the first trial only, as this cannot be influenced by any previous trials.…”
mentioning
confidence: 99%
“…We acknowledge the concerns noted about the approach of Rugani et al (Harshaw, 2015; Mangalam & Karve, 2015; Shaki & Fischer, 2015), but we wanted to present as close an approach in our first computerized experiment to what was done with the chicks in the open field test. And, our use of a computerized task, with highly proficient users of that apparatus, minimized or eliminated any concerns about specific motor and perceptual biases evident in chicks (Harshaw, 2015).…”
mentioning
confidence: 99%
“…Thus, these confounds with number may have accounted for the chicks' response biases. Harshaw (2015) argued that precocial chicks have natural perceptual and motoric biases that align with SNARC-like effects but for reasons unrelated to processing of numerical or quantitative information, and concerns were raised about the analyses that were applied to repeated-measures data collected from the chicks (Mangalam & Karve, 2015).…”
mentioning
confidence: 99%